The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21010/ajtcam.v14i3.29
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF CRUDE FLAXSEED (Linum usitatissimum L.) OIL IN BURN WOUND HEALING IN NEW ZEALAND RABBITS

Abstract: Background: Burns are among the most prevalent injuries in humans with high cost in health care and heavy prolonged or permanent physical, psychological and social consequences. Commercial antimicrobial creams and dressing agents are unsuccessful in healing deep burn wounds. Materials and Methods: A study was conducted to assess the impact of crude linseed oil (LSO) topical application on burn wounds healing in rabbits in comparison with untreated wounds (NAT) and those treated with Vaseline gel (VAG) and Cica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
1
13
1
1
Order By: Relevance
“…Throughout the study, burns treated with linseed oil were found to be healing faster and showed significantly higher wound contraction than the control treatments. Less inflammatory cells, complete epithelial regeneration with a reduced thickness of the newly formed dermis, fibrosis, enhanced neovascularisation, and an increased number of collagen fibres, fibroblasts, and myofibroblasts were observed in wounds treated with linseed oil (Beroual et al, ).…”
Section: Polyunsaturated Fatty Acid‐based Oilsmentioning
confidence: 99%
“…Throughout the study, burns treated with linseed oil were found to be healing faster and showed significantly higher wound contraction than the control treatments. Less inflammatory cells, complete epithelial regeneration with a reduced thickness of the newly formed dermis, fibrosis, enhanced neovascularisation, and an increased number of collagen fibres, fibroblasts, and myofibroblasts were observed in wounds treated with linseed oil (Beroual et al, ).…”
Section: Polyunsaturated Fatty Acid‐based Oilsmentioning
confidence: 99%
“…• Fixedoil [139] • α-linolenicacid [139,140] • Tocopherol(vitaminE) [141] •Flaxseedoil [142] •Flaxseedhulloil [143] • Pteroleumetherseedsextract containing palmitic acid, linoliec acid and oleic acid [144] •Fixedoil [145] • Fixedoil [117,141,[146][147][148] • α-Linolenic acid-rich linseedoil [149] • Oleicacid [150] • linoleicacid [146,150] • α-Linolenic acid [146,149,150]…”
Section: Linum Usitatissimum Seeds Oilmentioning
confidence: 99%
“…L. usitatissimum seeds fixed oil was found to inhibit the prostaglandin 2-, leukotriene-, histamine-, bradykinin-, and arachidonic acid-induced inflammation [139]. L. usitatissimum seeds constituents, α-linolenic acid and tocopherol, have been shown to inhibit COX and LOX pathways [140] and to attenuate proinflammatory cytokines and chemokines production [141], respectively. M. communis leaves essential oil, topically applied, was found to inhibit the migration of neutrophils to the inflamed area and the TNF-α and IL-6 formation [155].…”
Section: Thymus Laevigatus Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ficus asperifolia, Bridelia ferruginea, Gossypium arboreum [3], Cucurbita moschata [50], Linum usitatissimum L. [51], Sesamum indicum L., Pistacia atlantica Desf., Cannabis sativa L., Juglans regia L. [52], Scutellariae (altissimae, galericulatae, hastifoliae) [53].…”
Section: Centella Asiaticaunclassified